2018
DOI: 10.1097/wnr.0000000000001118
|View full text |Cite
|
Sign up to set email alerts
|

MiR-16 attenuates β-amyloid-induced neurotoxicity through targeting β-site amyloid precursor protein-cleaving enzyme 1 in an Alzheimer’s disease cell model

Abstract: The aberrant deposition of β-amyloid (Aβ) is closely linked to the pathogenesis and development of Alzheimer's disease (AD). MiR-16 was abnormally downregulated and may be related to the development of AD. However, the functional role and molecular mechanism of miR-16 in AD pathogenesis are still not well elucidated. The expressions of miR-16 and β-site amyloid precursor protein-cleaving enzyme 1 (BACE1) mRNA and protein levels in AD brain tissues and Aβ-treated PC12 cellular AD model were examined by qRT-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The expression of crucial miRNAs that are potentially involved in regulating the expression of BACE1 appears to be decreased in the brains of patients with AD. For instance, the expression of miR-107, miR-29a/b-1, miR-29c, miR-188-3p, miR-339-5p, miR-195, miR-186, and miR-16 is decreased in the brains of patients with AD and AD mice (Hebert et al, 2008;Zhu et al, 2012;Long et al, 2014;Zhang J. et al, 2014;Lei et al, 2015;Jiao et al, 2016;Kim et al, 2016;Zhong et al, 2018). Studies have confirmed that these miRNAs regulate BACE1 expression levels by targeting the 3 -UTR region of the BACE1 mRNA.…”
Section: The Role Of Mirnas In Regulating Bace1mentioning
confidence: 96%
“…The expression of crucial miRNAs that are potentially involved in regulating the expression of BACE1 appears to be decreased in the brains of patients with AD. For instance, the expression of miR-107, miR-29a/b-1, miR-29c, miR-188-3p, miR-339-5p, miR-195, miR-186, and miR-16 is decreased in the brains of patients with AD and AD mice (Hebert et al, 2008;Zhu et al, 2012;Long et al, 2014;Zhang J. et al, 2014;Lei et al, 2015;Jiao et al, 2016;Kim et al, 2016;Zhong et al, 2018). Studies have confirmed that these miRNAs regulate BACE1 expression levels by targeting the 3 -UTR region of the BACE1 mRNA.…”
Section: The Role Of Mirnas In Regulating Bace1mentioning
confidence: 96%
“…PC12 cells induced by Aβ 1–42 was established as a ell model (Zhong et al., 2018). Aβ 1–42 (Sigma‐Aldrich) was dissolved in double distilled water to prepare a 0.5 mM storage solution and then frozen at −20℃.…”
Section: Methodsmentioning
confidence: 99%
“…miR-338-5p also regulates BACE-1 expression by targeting its mRNA, and expression of this micro-RNA leads to increased Aβ formation in brain tissues [122]. Downregulated miR-29a/29b1/c, miR-338-5p and miR-16 are all linked to increased Aβ-mediated neurotoxicity in vitro and in vivo [113]. Among those microRNAs, miR-338-5p also regulates NF-kB signaling and promotes neuroinflammation [122].…”
Section: Ncrnas In the Regulation Of Aβ Generation And Accumulationmentioning
confidence: 99%